2018
DOI: 10.22533/at.ed.314181009
|View full text |Cite
|
Sign up to set email alerts
|

Ultrassom na indústria de alimentos: aplicações no processamento e conservação

Abstract: Alimentos-Indústria. I. Prudencio, Elane Schwinden. II. Título. CDD 664.005 Elaborado por Maurício Amormino Júnior-CRB6/2422 O conteúdo do livro e seus dados em sua forma, correção e confiabilidade são de responsabilidade exclusiva dos autores. 2018 Permitido o download da obra e o compartilhamento desde que sejam atribuídos créditos aos autores, mas sem a possibilidade de alterá-la de nenhuma forma ou utilizá-la para fins comerciais.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
(42 reference statements)
0
6
0
1
Order By: Relevance
“…Thus, it is possible to indicate the treatments evaluated here for microbiological control. It has been shown that microbial degradation by ultrasound action is due to the thinning of cell membranes, production of free radicals and localized heating, as well as the generation of intracellular cavitation (mechanical shocks start to break structures up to cell lysis), confirming the effectiveness of ultrasonication and thermosonication processes as commercial sterilization methods (Verruck and Prudencio, 2018).…”
Section: Microbiological Characterizationmentioning
confidence: 92%
“…Thus, it is possible to indicate the treatments evaluated here for microbiological control. It has been shown that microbial degradation by ultrasound action is due to the thinning of cell membranes, production of free radicals and localized heating, as well as the generation of intracellular cavitation (mechanical shocks start to break structures up to cell lysis), confirming the effectiveness of ultrasonication and thermosonication processes as commercial sterilization methods (Verruck and Prudencio, 2018).…”
Section: Microbiological Characterizationmentioning
confidence: 92%
“…Some efforts have been made trying to expand this multifaceted technology to industrial scale, aiming the same efficacy presented at laboratorial experiments (Verruck & Prudencio, 2018). The “green aspect” and relatively low cost of US (i.e., comparing to energy consumption and solvent waste that generally are associated with conventional processing technologies) make it an essential component in research laboratories and a potential tool for food industry (Zhou, Zhang, Xing, & Zhang, 2021).…”
Section: Future Prospects To Ultrasound In Food Industrymentioning
confidence: 99%
“…A great number of studies have proved the effectiveness of US in replacing and enhancing various conventional processes in the food industry (Bhargava et al, 2020). US becomes even more efficient when associated with other processes, promoting an increase in the efficiency (i.e., reducing processing time) of some industrial operations such as drying, extraction, crystallization, homogenization, filtration, fermentation, enzymatic, and microbiological inactivation (Campo‐Vera et al, 2018; Singla & Sit, 2021; Verruck & Prudencio, 2018). In general, the association of US with other conventional technologies gives positive results in the overall quality of the final product and may represent the first step to further research (Bhargava et al, 2020).…”
Section: Future Prospects To Ultrasound In Food Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Figura 1 -Faixa de frequência das ondas sonoras. (Fonte: Verruck e Prudêncio [142]). ..... 46 Figura 2 -Esquema da experimentação, com uso da técnica pulso eco.…”
Section: Lista De Figurasunclassified